Toward An Understanding of Plurality: A Case Study of Teaching and Learning English as an International Language (EIL) Approach in an Indonesia Senior High School - Susi Andriani Simanjuntak; Hsi-Nancy Lien (Universitas Muhammadiyah Kalimantan Timur, 2021)
In this research study, there were 6 English teachers and two classes (Grade 1 and Grade 2, approximately with 60 students) were interviewed designed to gain an understanding of both English teachers and students’ perspectives on English as international language (EIL). There is a hegemony concepts about English perspective impart among the students and the teachers in this research community, that is native norm is the center, the most prestigious, endowed with a sense of authenticity and authority. These issues make them afraid to make any risk, little faith to apply EIL that created two different worlds of English standard and nonstandard English. From the result of the study, there are some pedagogical Implications of EIL Teaching Approach Contribution in Indonesia. They are EIL teaching required change of mind set in terms of understanding EIL model, the history and English today, and empowering Nonnative English teachers and general Public.